Terrestrial Plants Evolve Highly Assembled Photosystem Complexes in Adaptation to Light Shifts - Chen, Yang-Er; Su, Yan-Qiu; Mao, Hao-Tian; Wu, Nan; Zhu, Feng; Yuan, Ming; Zhang, Zhong-Wei; Liu, Wen-Juan; Yuan, Shu (Frontiers in Plant Science, 2018)
It has been known that PSI and PSII supercomplexes are involved in the linear and cyclic electron transfer, dynamics of light capture, and the repair cycle of PSII under environmental stresses. However, evolutions of photosystem (PS) complexes from evolutionarily divergent species are largely unknown. Here, we improved the blue native polyacrylamide gel electrophoresis (BN-PAGE) separation method and successfully separated PS complexes from all terrestrial plants. It is well known that reversible D1 protein phosphorylation is an important protective mechanism against oxidative damages to chloroplasts through the PSII photoinhibition-repair cycle. The results indicate that antibody-detectable phosphorylation of D1 protein is the latest event in the evolution of PS protein phosphorylation and occurs exclusively in seed plants. Compared to angiosperms, other terrestrial plant species presented much lower contents of PS supercomplexes. The amount of light-harvesting complexes II (LHCII) trimers was higher than that of LHCII monomers in angiosperms, whereas it was opposite in gymnosperms, pteridophytes, and bryophytes. LHCII assembly may be one of the evolutionary characteristics of vascular plants. In vivo chloroplast fluorescence measurements indicated that lower plants (bryophytes especially) showed slower changes in state transition and nonphotochemical quenching (NPQ) in response to light shifts. Therefore, the evolution of PS supercomplexes may be correlated with their acclimations to environments.